Correction of ocean hemispherical spectral reflectivity for longwave irradiance computations. (March 2016) - Ham, Seung-Hee; Kato, Seiji; Rose, Fred G.
Abstract: This study demonstrates that upward infrared irradiances have negative modeling biases when the ocean hemispherical spectral reflectivity is used. The biases increase with increasing air temperature and with decreasing water vapor amount. Spectral biases in the surface upward longwave irradiance from 4 μm to 80 μm are between −0.4 and 0 W m −2  μm −1, while longwave broadband biases are between −2 and −1 W m −2 . The negative biases stem from surface-reflected component because an irradiance radiative transfer model ignores the correlation between the downward radiance and directional reflectivity. Therefore, a positive correction factor to the hemispherical spectral reflectivity for the irradiance radiative transfer model is needed. A simple parameterization using an anisotropic factor for downward radiances is developed to correct reflectivity for various atmospheric conditions.